The first recording of leaf blight disease Defla in Iraq (Baghdad Science Journal, 2005)
The results showed the spread of disease blight leaves caused by injury fungus Alternaria in different areas of cultivation in the city of Baghdad where he was recording the highest rate and the severity of the disease of 100% and 80%, respectively, in the Abu Ghraib area and the least of 20% and 12% respectively in the Amiriya district results showed test pathogenicity of the fungus pathogen emergence of symptoms of the disease superficial discoloration Authority of black paper when wound areas and yellowing of leaves about race as centrist and leaky latest country clear ????? on Central race after 48 hours ....